Optimalisasi Pembelajaran PJOK Berbasis Digital melalui Aplikasi Analisis Gerak di SMK Negeri 14 Medan - Aprial. M, Benny; Alhumary, Farid M; Nasution, Alwi Fahruzy; Siregar, Imanuddin; Repiyasa, I Wayan; Rahman, Arief; Gunawan, Andi; Gulo, Syukur Putra Abadi; Zlukhu, Anuarman (Jurnal Inovasi Olahraga, 2026)
The digital transformation in education requires the integration of technology into learning processes, including Physical Education. However, conventional Physical Education learning still relies on subjective observation methods with limited accuracy in analyzing students’ movements. This community service program aimed to optimize digital-based Physical Education learning through motion analysis applications at SMK Negeri 14 Medan. The method used was the ORPAER model (Observe, Reflect, Plan, Action, Evaluate, Reflect), implemented in four cycles: pre-service, training, field implementation, and evaluation. Data were collected through observation, interviews, and documentation, then analyzed using descriptive percentage techniques. The results showed an increase in teachers’ competence from 33% to 86% (161% improvement), as well as improved learning quality with a score of 3.6 (good category). The program also enhanced student engagement and self-directed learning. Therefore, the ORPAER model effectively improves teachers’ technological pedagogical competence and digital-based Physical Education learning quality.